Effect of Certificate of Bank Indonesia Sharia and Indonesian Bank Seven Days Repository Rate to Inflation Ratio in Indonesia During Covid-19 Pandemic - Inayah Rahman; Ririn Tri Ratnasari; Akhmad Kusuma Wardhana (FKIP Universitas Lampung, 2022)
Inflation that is too low can disrupt economic stability. The new benchmark interest rate by BI, BI7DRR is expected to increase the effectiveness of monetary policy to achieve the inflation target set. Meanwhile, SBIS is one of BI's alternatives to regulate inflation in Indonesia. This study aims to observe the effect of SBIS and BI7DRR on inflation in Indonesia for the 2019-2020 period. the data were gathered from Bank Idonesia website using purposive sampling method. The independent variables in this study are BI7DRR and Indonesian bank of sharia certificate SBIS, while the dependent variable is inflation. This study used eroor correction model (ECM) to determine the effect of independent variables to dependent one. The data was monthly time series period started from January 2019 to December 2020. The results showed that there was a significant effect between the return value of the SBIS to Indonesia's inflation rate.